The Allure and the Paucity of Design: Cultures of Design and Design in Culture. (2nd January 2021) - Dourish, Paul
Abstract : Human–computer interaction (HCI) has traditionally framed itself as a design-oriented discipline. This position, in turn, frames design as HCI's primary tool for intervening or producing change in the world. By taking up two apparently contradictory suggestions—that there is less design in the world than there might seem, and that there is more of it around than ever before—this article examines the limits and rhetorics of design in HCI and in the broader cultural settings within which HCI is embedded.